Exploring the correlation regarding strong maternal attachment and knowledge of early childhood development - Sinem Başdemir; Hatice Yıldırım Sarı (Journal of Infant, Child and Adolescent Health, 2026)
Purpose: The study aims to investigate the correlation of maternal attachment with knowledge of early childhood development. Method: In this correlational study, data were collected from 211 mothers having children aged 1-24 months in the pediatric outpatient clinics of two hospitals using a parent-infant information form, the Maternal Attachment Inventory, and the Caregiver Knowledge of Child Development Inventory. Results: The study revealed a statistically significant positive correlation between the Maternal Attachment Inventory and the Caregiver Knowledge of Child Development Inventory. In the regression analysis, an increase in the Maternal Attachment Inventory by one point increased the score of the Caregiver Knowledge of Child Development Inventory by 0.268 units. Conclusion: It was concluded that maternal attachment increased mothers' knowledge of early childhood development. Mothers with strong attachments to their infants may seek more child development knowledge that enables their sensitive caregiving.